2015
DOI: 10.4028/www.scientific.net/amm.725-726.153
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of High-Rise Complex Construction Depending on Building Site Placement

Abstract: Construction industry is an influential element of Russian economy. It is well known that the main objective of construction for a builder is receiving profit in the form of a difference between the received investment contributions and size of construction cost. Therefore maximum efficiency from implementation of a project will be received by a builder who will carry out construction of the most investment-attractiveness object.Investors do not use certain formalized analytical tools for assessment of situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
“…Secondary building of the territory by high-rise buildings is a convenient way of renovation of quarter by means of which conditions of accommodation of the population improve, the quantity of shabby housing in the area decreases, there are large volumes of new inhabited space, and, therefore, and security of the population with housing increases, the infrastructure and improvement of the territory improves. Thus it isn't required development of new territories, because the site of building remains within the available borders [3]. Authors of this article made an attempt to consider a possibility of renovation of the quarter which is situated in Nevskiy district in the territory limited to streets Karavayevsky and Teplovoznoy, Slepushkin and Skachkov's lanes and makes 141129.6 sq.m (see fig.…”
Section: Concept Of Renovation Of Housing Stock Justification Of a Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In these papers the assessment of technical conditions determined on the basis of: the theory of risk and structural safety [16], the logical-probabilistic approach [17], based on a combination of probabilistic and possibility approaches [18], based on the application of the theory of fuzzy sets [19,20] and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Tall buildings have a high partial pressure of steam on the upper floors. In this case, the vapor barrier properties of the fence, even made of cast concrete, may not be enough, need more steam, [1,15] With regard to the ventilated facade weight loss of mineral wool installed without wind and waterproof membrane, leads not only to a decrease in strength, thermal insulation properties, but also to a serious violation of the ecology of the environment and living space. For example, a nine-storey building with insulation Series 90, with an area of 1498 square meters of insulation.…”
Section: Introductionmentioning
confidence: 99%